Pengurbanan Kerbau pada Upacara Rambu Solo Masyarakat Toraja: Identifikasi Karakteristik untuk Mendukung Pelestarian Budaya - Tangkeliku, Augustine Sem Porak; Irianto, Sulistyowati (LPPM Universitas Trunojoyo Madura, 2023)
The buffalo-fighting rituals in Rambu Solo's funeral ceremony in Tana Toraja and North Toraja illustrates continuity and change in that community and the state of and alteration in economic stratification in Toraja. The number and type of buffaloes sacrificed at a funeral indicate the social class of the participants. Before the buffaloes are slaughtered, they are pitted against each other in a ritual fight to console the grieving family. This study was performed using ethnographic methods. It relied on participant observation and in-depth interviews. There are social gaps in funeral rituals in Toraja. However, the class itself is shifting. Previously, expensive events involving the sacrifices of many buffaloes were privileged to noble families. However, the ability to hold such ceremonies is open to anyone possessing wealth. Wealthy families who are not from noble lines can also hold such ceremonies. Contemporary ceremonies now feature gambling on buffalo fights. The fact that a buffalo-fighting arena is present at a funeral ceremony indicates the presence of gambling. Furthermore, such arenas can be expected to accompany the planned sacrifice of a large number of buffaloes. The increased presence of buffalo-fighting arenas and gambling at funeral ceremonies constitutes a new signifier for funeral ceremonies in Toraja.